The Influence of Facebook, Youtube and Instagram Social Media Marketing On The Number of Outpatient Visits at UKRIDA Hospital Jakarta - Tarumingkeng, Lingkan; Rumambi, Freddy J; Tangkudung, Auderey GD (LPPM Universitas PGRI Sumatera Barat, 2024)
Currently, many new hospitals are being built in Indonesia, which has led to increased competition in the world of hospitals. To survive, hospitals must increase their efforts to attract customers. UKRIDA Hospital in Jakarta, as a relatively new hospital, has also carried out various marketing efforts to attract patients to visit and seek treatment at UKRIDA Hospital. The very rapid development of digital technology has triggered changes in various aspects of health services, one of which is the marketing aspect, namely by carrying out marketing activities for health facilities and services through social media platforms. UKRIDA Hospital is aware of this development and has carried out marketing efforts on various social media platforms, including Facebook, YouTube and Instagram. This research intends to see how much influence marketing on the three social media platforms has on the number of outpatient visits. This Research on the Influence of Facebook, YouTube and Instagram Social Media Marketing on the Number of Outpatient Visits at UKRIDA Hospital in Jakarta is a quantitative research and the method of analysis used is the Structural Equation Model (SEM) with the SmartPLS program. The sample in this study is 100 UKRIDA Hospital adult outpatients and the research was conducted during the period of September - October 2024, using questionnaires as the data collection technique. Based on research results, Instagram social media marketing is proven to have a significant influence on the number of outpatient visits at UKRIDA Hospital in Jakarta, while Facebook and YouTube did not show a significant influence. The R-Square value obtained was 0.292, which means that apart from Instagram social media marketing, there are still many other factors that influence the number of UKRIDA Hospital outpatient visits.